The Role of AI and Strategic Management in the Sustainable Digital Transformation of the Iranian Telecommunications Industry - Moradi, Naser (Digital Repository of Theses - SSBM Geneva, 2025)
According to the increase in the part of data and income of machinists, the telecommunications manufacturing has knowledgeable quick changes at the global level. While the mobile and mobile broadband development indicators in Iran are still lower than in many other parts of the world, they have shown signs of significant growth in recent years and have created great opportunities for newcomers and opportunists. Iran, as one of the largest markets in the Middle East, by implementing global technologies and improving the domestic situation, has great potential to increase the share of information and communication technology in the GDP and may enter an important digital transformation soon. Addressing the role of artificial intelligence and strategic management in the sustainable DT of Iran's telecommunications industry is very vital. This industry is very important in Iran because the use of artificial intelligence technology in Iran's telecommunications industry has advantages that can help improve various functions in this industry, including improving service quality, optimizing processes, predicting customer needs, and increasing Efficiency. Considering the high dynamism of the telecommunications industry and the need to quickly respond to market and technology developments, correct strategic management can help create appropriate strategies and their efficient implementation. Paying attention to the forward trend of digital transformation and sustainability in the telecommunications industry, the use of new technologies to better manage resources, reduce costs, and increase the speed and quality of services is expected. Therefore, focusing on the task of artificial intelligence and strategic management in the sustainable DT of Iran's telecommunications industry can help improve the performance and competitiveness of this industry at the national and international levels. This exploratory study was developed in Swiss School of Business and Management with the primary goal of pinpointing evaluates the simultaneous effect of artificial intelligence and strategic management for sustainable digital transformation for Iranian Telecommunication companies.